Pengaruh Cetakan Terhadap Hasil Kericu Pada Mesin Pembuat Kericu - Irawan, Terris; Wahyudie, Illham Ary; Husman, Husman (Politeknik Manufaktur Negeri Bangka Belitung, 2025)
The Bangka Belitung Islands consist of two main islands, namely Bangka Island and Belitung Island, which have abundant marine natural resource potential. One of the typical products of the seafood is Kericu, which is a snack made from squid eggs and sago. Kericu has become a special souvenir that is in demand and has become a home-based business opportunity. UMKM